Comparison of the Solution and Vacuum-Processed Squaraine:Fullerene Small-Molecule Bulk Heterojunction Solar Cells - Chen, Guo; Ling, Zhitian; Wei, Bin; Zhang, Jianhua; Hong, Ziruo; Sasabe, Hisahiro; Kido, Junji (Frontiers in Chemistry, 2018)
Squaraine dyes have shown promising properties for high performance organic solar cells owing to their advantages of intense absorption and high absorption coefficients in the visible and near-infrared (NIR) regions. In this work, to directly compare the photovoltaic performance of solution- and vacuum-processed small-molecule bulk heterojunction (SMBHJ) solar cells, we employed a squaraine dye, 2,4-bis[4-(N,N-diisobutylamino)-2,6-dihydroxyphenyl] squaraine (DIBSQ), as an electron donor combined with fullerene acceptors to fabricate SMBHJ cells either from solution or vacuum deposition process. The solution-processed SMBHJ cell possesses a power conversion efficiency (PCE) of ~4.3%, while the vacuum-processed cell provides a PCE of ~6.3%. Comparison of the device performance shows that the vacuum-processed SMBHJ cells possess higher short-circuit current density, fill factor and thus higher PCE than the solution-processed devices, which should be assigned to more efficient charge transport and charge extraction in the vacuum-processed SMBHJ cells. However, solution-processed SMBHJ cells demonstrate more pronounced temperature-dependent device performance and higher device stability. This study indicates the great potential of DIBSQ in photovoltaic application via both of solution and vacuum processing techniques.